Exploring tertiary English teachers’ emotions during their teaching practice: a case study - Wong Barragan, Lesly Carolina; dos Santos, Jardel Coutinho (Arandu UTIC, 2025)
This study explored the emotions experienced by two English teachers at a public university in Ecuador and how these emotions influence their teaching practice and professional well-being. Through interviews, observations, and visual narratives, both pleasant emotions such as enthusiasm and joy, and unpleasant emotions such as nervousness, frustration, sadness, and stress were identified. The teachers used various emotion regulation strategies, including breathing exercises and not taking situations personally, to maintain their resilience. While one teacher showed consistent emotional stability, both faced emotional challenges related to administrative responsibilities, family loss, and student behavior. The findings highlight the importance of acknowledging teachers’ emotional dimensions and supporting the development of skills to manage emotions in complex educational contexts with multiple demands.